The Lecturer's and College Students' Need Toward Schoology-Based Student Worksheet - Onas, Fernando; Nurhayati; Mukmin, Suhardi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Teaching materials can improve students' writing skills. However, in developing teaching materials, it is necessary to understand the needs of students. This study aims to analyze the needs of students and lecturers in writing drama scripts. This qualitative research analyzes the first stage of the Research and Development design. The approach used is qualitative. The methods used in collecting data are interviews and questionnaires. The research subjects were 20 students. The technique used in analyzing the data is the qualitative analysis technique. The findings show that they need student worksheets that can motivate, collaborate, increase enthusiasm for learning, facilitate, provide time for asking questions, provide feedback, have clear instructions, and can be accessed anywhere. This study recommends Schoology as the solution. On the other hand, lecturers need technology-based tools to support their creativity and provide feedback for students anywhere, even outside the classroom. Therefore, Schoology, as an innovative learning media platform, can be used to meet the needs of lecturers and students. The platform is practical for both parties and can be accessed from a browser installed on a laptop computer or mobile phone. With all these advantages and disadvantages, Schoology becomes an alternative for the needs of lecturers and students to learn and teach writing poetry-based drama scripts.